GENDER DIFFERENCES IN PARITY-SPECIFIC FERTILITY TRANSITION MODELS - Ecaterina Grigoraș (Economy and Sociology)
Most demographic studies focus on the reproductive behavior of women, leaving a gap in the understanding of male demographic fertility. New fertility patterns in recent decades and the increasing involvement of men in family planning and the number of children within a couple have provided solid grounds for analyzing male reproductive behavior in investigating fertility determinants. The study aims to explore the differences in parity patterns between men and women in Moldova, comparing the age at which men become parents for the first time, the number of biological children over their lifetime, and the transition to the first, second, and third child. Using data from the Generations and Gender Survey conducted in 2020, the research focuses on cohorts of men and women born between 1950 and 1989. To test the hypotheses that men have a longer reproductive lifespan, start their reproductive activity later than women, and registers a higher number of biological children, the following methodologies are employed: Analysis of the mean number of biological children for selected birth cohorts 1950-1985; Determination of the proportion of men who remain childless by the end of life and the proportion of women who remain childless by the end of the reproductive period; Evaluation of the transition to the birth of children of different parities for men and women using probability models. The results indicate significant gender differences: men become parents, on average, three years later than women and have a lower average number of children over their lifetime. Additionally, the proportion of men who remain childless throughout their lives is significantly higher compared to women who have completed their reproductive period. These findings suggest substantial differences in the reproductive behavior of men and women, contributing to a broader and more complete picture of population dynamics and fertility trends.